Pengembangan E-Modul Biologi Terintegrasi Al-Qur’an untuk Meningkatkan Berpikir Kritis Siswa - Rima Anggraini; Syarifah Widya Ulfa (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop a science literacy-based biology e-module integrated with Qur’anic verses on the human respiratory system topic to improve high school students’ critical thinking skills. This study used a Research and Development (R&D) method with the 4D model, consisting of Define, Design, Develop, and Disseminate stages. The trial subjects involved 25 eleventh-grade students and a team of expert validators. The data collection instruments consisted of validation sheets, user response questionnaires, and a test instrument comprising six essay questions based on Facione’s critical thinking indicators. The results showed that the developed e-module was categorized as highly valid, with validity percentages of 95.04% from media experts, 95.63% from material experts, and 89.29% from Qur’anic integration experts. The product was also categorized as highly practical based on teacher responses of 97.92% and student responses of 91.86%. Furthermore, the e-module was proven effective in improving students’ critical thinking skills, increasing the average score from 50.44 to 82.92, with an N-Gain index of 0.66, which was categorized as moderate. Therefore, the science literacy-based e-module integrated with Qur’anic verses was declared feasible, highly practical, and effective in improving students’ critical thinking skills, as well as contributing positively to harmonizing science and faith. Keywords: Critical Thinking, E-Module, Integration of the Qur’an, Respiratory System, Science Literacy